A boundary integral equation related to the riemann map and the riemann problem - S. Nasser, Mohamed M. (2003)
The Riemann problem is very useful for the understanding of equations like Euler conservation equations because all properties, such as shocks and rarefaction waves, appear as characteristics in the solution. It also gives an exact solution to some complex nonlinear equations, such as the Euler equations.